Respuesta :

Answer: 4x^3 - x^2 - 20x + 5

Step-by-step explanation:

The given functions are

g(x) = 4x - 1

h(x) = x^2 - 5

We want to determine g(x).h(x)

We do this by multiplying g(x) by h(x). It becomes

g(x).h(x) = (4x - 1)(x^2 - 5)

We will expand the bracket by multiplying each term in the bracket . it becomes

(4x × x^2) + (4x × -5) + (-1 ×x^2) +

(-1 × - 5)

= 4x^3 - 20x - x^2 + 5

We would rearrange it in the standard form of a polynomial. It becomes

= 4x^3 - x^2 - 20x + 5

ACCESS MORE